Prevalence of postpartum depression and its associated factors within a year after birth in Semey, Kazakhstan: A cross sectional study - Madina Abenova; Ayan Myssayev; Lucy Kanya; Maria Nicoleta Turliuc; Ulzhan Jamedinova (Elsevier, 2022)
Background: Postpartum depression (PPD) is a depressive disorder that occurs after childbirth and can last until a year after delivery. The global prevalence of PPD among mothers is between 0.5% and 63.3%. The aim of the study is to determine the prevalence of postpartum depression within a year after birth among mothers in Semey (Kazakhstan) and identify the factors associated with it. Methods: A cross-sectional study covering 251 women within one year after delivery was conducted in five Primary Healthcare Centers in Semey. The Edinburgh Postnatal Depression Scale (EPDS) for assessing PPD was used. Data was analysed using the Statistical Package for Social Sciences (SPSS), version 25. The statistical significance and magnitude of the relationships between dependent and independent variables were conducted using chi-square and bivariate and multivariate logistic regression analyses. A p-value of less than 0.05 was considered to be significant. Results: The prevalence of PPD within a year after delivery was estimated as 59.4%. Factors including accommodation type (p = 0.021), satisfaction with living conditions (p = 0.001), relationship with mother-in-law (p = 0.013), the interest of the patronage service about the psychological state of a woman after childbirth (p = 0.001) and husband employment status (p = 0.04) showed significant positive association with PPD. Conclusion: The high prevalence rate of PPD and associated risk factors imply the need for strengthening and improving of postpartum care program in country. Further research on the experiences and the level of antenatal depression among women will be needed to understand and prevent any possible depressions in prenatal and postpartum periods.